2021
DOI: 10.1186/s12903-021-01728-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing international and U.S. dentists’ interest in advanced periodontal education: a pilot study

Abstract: Background The enrollment of international periodontal students in U.S. dental schools has been increasing in recent years. Interest in applying to a periodontics specialty program may differ between U.S and international dental school graduates. The purpose of this study is to assess, from the perspective of periodontal residents, (1) factors that interest dental students to apply to periodontics programs and (2) differences in background and interest between U.S and international graduates. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…10 Furthermore, a study surveyed Periodontics Department Chairs and described a significant association between periodontics rotations where students interact with periodontists and the pursuit of an advanced periodontal education. 11 The top influential factors in applying for residency from the student's standpoint were earlier exposure to periodontal procedures and increased contact with periodontists. Student surveys have found that mentoring encouraged students to pursue specialty training.…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, a study surveyed Periodontics Department Chairs and described a significant association between periodontics rotations where students interact with periodontists and the pursuit of an advanced periodontal education. 11 The top influential factors in applying for residency from the student's standpoint were earlier exposure to periodontal procedures and increased contact with periodontists. Student surveys have found that mentoring encouraged students to pursue specialty training.…”
Section: Discussionmentioning
confidence: 99%